2017
DOI: 10.1007/s00059-017-4591-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between inducible NOS single-nucleotide polymorphisms and hypertension in Han Chinese

Abstract: The current study provides evidence that iNOS is strongly associated with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Of particular interest in the context of this review are works in which the NOS1, NOS2, and NOS3 genes SNVs were considered as risk factors for several comorbid disorders, including AH and M or associated conditions. + [23] rs2779249 - [11,12] +* [11] + [26,27] - [25] +* [25,26] rs2297518 - [11,12] +* [11,12] + [25,27] - [26] +* [25,26] NOS3 rs148554851 - [18] -* [18] rs1799983 + [13,17,20] - [8,10,12,14,15,18] -* [14,15,18] + [30,34] ± [24] - [28,29,[31][32][33]35] +* [30,32]-* [31] rs1800779…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest in the context of this review are works in which the NOS1, NOS2, and NOS3 genes SNVs were considered as risk factors for several comorbid disorders, including AH and M or associated conditions. + [23] rs2779249 - [11,12] +* [11] + [26,27] - [25] +* [25,26] rs2297518 - [11,12] +* [11,12] + [25,27] - [26] +* [25,26] NOS3 rs148554851 - [18] -* [18] rs1799983 + [13,17,20] - [8,10,12,14,15,18] -* [14,15,18] + [30,34] ± [24] - [28,29,[31][32][33]35] +* [30,32]-* [31] rs1800779…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the OR was 1.27 (95% CI 1.12-1.44) in the additive model, 1.31 (1.09-1.59) in the dominant model, and 1.68 (1. 28-2.19) in the recessive model rs2779249; and 1.26 (1.06-1.50) in the additive model and 1.46 (1.13-1.89) in the dominant model rs2297518 [27].…”
Section: Gene Nos2mentioning
confidence: 99%
“…iNOS variant rs2779249 (-1026 C>A) is also located in the promoter region of the gene and it has been shown that nucleotide change from C to A increases iNOS promoter transcriptional activity to five-fold leading to higher NO production [22]. This SNP has been associated with hypertension in Chinese Han population and with rheumatoid arthritis in Indians [23,24]. For the -954G>C polymorphism, the substitution of G to C results in a phenotype with a seven-fold higher baseline NOS activity [25].…”
Section: Discussionmentioning
confidence: 99%